2021
DOI: 10.1111/cdev.13517
|View full text |Cite
|
Sign up to set email alerts
|

Parental Job Loss and Early Child Development in the Great Recession

Abstract: The study examines whether and why parental job loss may stifle early child development, relying on cohort data from the population of children born in Ireland in 2007-2008 (N = 6,303) and followed around the time of the Great Recession (2008)(2009)(2010)(2011)(2012)(2013). A novel approach to mediation analysis is deployed, testing expectations from models of family investment and family stress. Parental job loss exacerbates problem behavior at ages 3 and 5 (.05-.08 SDs), via the channels of parental income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
(181 reference statements)
1
10
0
Order By: Relevance
“…Firstly, for the prenatal stress assessment we just assessed pregnancy-related anxiety and did not include other modes of prenatal stress (e.g. life events, depression) or stress at postpartum; these forms of stress, which also predict child behavioral and emotional development, were therefore not controlled during our analysis [49,50]. Secondly, our data showed that hyperactivity is more common among males (male:female = 19.4:13.2%; P < 0.05) and we cannot rule out the possibility that there is more scope to detect associations between pregnancy-related anxiety and hyperactivity in males.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, for the prenatal stress assessment we just assessed pregnancy-related anxiety and did not include other modes of prenatal stress (e.g. life events, depression) or stress at postpartum; these forms of stress, which also predict child behavioral and emotional development, were therefore not controlled during our analysis [49,50]. Secondly, our data showed that hyperactivity is more common among males (male:female = 19.4:13.2%; P < 0.05) and we cannot rule out the possibility that there is more scope to detect associations between pregnancy-related anxiety and hyperactivity in males.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously parents may be less supportive and engage in children's homework and school-related activities. Mari and Keizer (2021) and Hill, Morris, Castells, and Walker (2011) also argued a similar concern about the linkage between parents' job loss and child development. Results show that income loss of parents triggers depression, and it leads to negative maternal parenting, which resulted in problem behaviour in children and reduced verbal ability during the early childhood period.…”
Section: The State Of Unemploymentmentioning
confidence: 96%
“…Income support for parents who need to take time away from work to care for their children has been identified as a policy solution to help parents balance care responsibilities during school and childcare center closures while maintaining income security and employment ( Gromada et al, 2020 ; Mizumoto et al, 2013 ; Zheteyeva et al, 2017 ). Ensuring economic stability for families, especially those already living month to month, and preventing parental job loss, particularly during times of economic downturn, matters to children’s health and educational outcomes in the short and long-term ( Gregg et al, 2012 ; Mari and Keizer, 2021 ; Ruiz-Valenzuela, 2020 ; Sigurdsen et al, 2011 ).…”
Section: Income Support During Absences From Work As a Policy Approachmentioning
confidence: 99%